DECAY: A Monte Carlo Library for the Decay of a Particle with ROOT Compatibility (Communications in Computational Physics, 2021)
Recently, there is a need for a general-purpose event generator for decaysof an elementary particle or a hadron to a state of higher multiplicity $(N ≥ 2)$ that issimple to use and universal. We present the structure of such a library for preparationof generators that generate kinematics of decay processes and can be used to integrateany matrix element squared over phase space of this decay. Some test examples arepresented, and results are compared with results known from the literature. As one ofexamples we consider the Standard Model Higgs boson decay into four leptons. Thegenerators discussed here are compatible with the ROOT interface.
Keywords: Monte Carlo; high energy physics; decay; Higgs decay; 4-Fermi theory.